Cognitive Decline in Neuronal Aging and Alzheimer's Disease: Role of NMDA Receptors and Associated Proteins - Avila, Jesús; Llorens-Martín, María; Pallas-Bazarra, Noemí; Bolós, Marta; Perea, Juan R.; Rodríguez-Matellán, Alberto; Hernández, Félix (Frontiers in Neuroscience, 2017)
Molecular changes associated with neuronal aging lead to a decrease in cognitive capacity. Here we discuss these alterations at the level of brain regions, brain cells, and brain membrane and cytoskeletal proteins with an special focus in NMDA molecular changes through aging and its effect in cognitive decline and Alzheimer disease. Here, we propose that some neurodegenerative disorders, like Alzheimer’s disease, are characterized by an increase and acceleration of some of these changes.